The Transcellular Propagation and Intracellular Trafficking of α-Synuclein - Tofaris, GK; Goedert, M; Spillantini, MG (Cold Spring Harbor Laboratory Press, 2016)
Parkinson’s disease is the second most common neurodegenerative disorder, with only partial symptomatic therapy and no mechanism-based therapies. The accumulation and aggregation of α-synuclein is causatively linked to the sporadic form of the disease, which accounts for 95% of cases. The pathology is a result of a gain of toxic function of misfolded α-synuclein conformers, which can template the aggregation of soluble monomers and lead to cellular dysfunction, at least partly by interfering with membrane fusion events at synaptic terminals. Here, we discuss the transcellular propagation and intracellular trafficking of α-synuclein and posit that endosomal processing could be a point of convergence between these two routes. Understanding these events will clarify the therapeutic potential of enzymes that regulate protein trafficking and degradation in synucleinopathies.